2019
DOI: 10.1093/ibd/izz104
|View full text |Cite|
|
Sign up to set email alerts
|

The Cost of Inflammatory Bowel Disease: An Initiative From the Crohn’s & Colitis Foundation

Abstract: Background The Crohn’s & Colitis Foundation’s Cost of Inflammatory Bowel Disease (IBD) Care Initiative seeks to quantify the wide-ranging health care costs affecting patients living with IBD. We aimed to (1) describe the annualized direct and indirect costs of care for patients with Crohn’s disease (CD) or ulcerative colitis (UC), (2) determine the longitudinal drivers of these costs, and (3) characterize the cost of care for newly diagnosed patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
206
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(216 citation statements)
references
References 21 publications
7
206
2
1
Order By: Relevance
“…While it was anticipated that patients with IBD and CID would incur higher costs than patients with CID alone, this study is the first to quantify the incremental costs and HRU associated with IBD among patients with AS, PsA, PsO, or RA, stratified by type of CID. Of note, the difference in total all-cause healthcare costs found in our study ($18,500) is similar to that observed in recent analyses which assessed the incremental burden of patients with IBD versus non-IBD controls (IBD: $16,031 [27], CD only: $17,463 [32], UC only: $11,029 [33]). Although comparisons with results from other analyses are prone to confounding, this suggests that the incremental burden associated with IBD in a population of patients with CID is similar to that observed in the general population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While it was anticipated that patients with IBD and CID would incur higher costs than patients with CID alone, this study is the first to quantify the incremental costs and HRU associated with IBD among patients with AS, PsA, PsO, or RA, stratified by type of CID. Of note, the difference in total all-cause healthcare costs found in our study ($18,500) is similar to that observed in recent analyses which assessed the incremental burden of patients with IBD versus non-IBD controls (IBD: $16,031 [27], CD only: $17,463 [32], UC only: $11,029 [33]). Although comparisons with results from other analyses are prone to confounding, this suggests that the incremental burden associated with IBD in a population of patients with CID is similar to that observed in the general population.…”
Section: Discussionsupporting
confidence: 89%
“…While multiple previous studies have assessed the incremental burden of IBD relative to controls without IBD [23][24][25][26][27], little is known on the burden of IBD in patients with pre-existing CID. A recent real-world analysis of the economic burden associated with IBD among patients with PsA and AS in the United States (US) showed that compared to patients without IBD, those with IBD had significantly higher total healthcare costs-up to 27% higher in patients with PsA and 38% higher among patients with AS [28].…”
Section: Introductionmentioning
confidence: 99%
“…When accounting for all medical therapy-related costs in IBD, biologic agents accounted for an impressive 85.7% of total costs. These findings have been confirmed across multiple studies, including a recent analysis conducted by the Crohn's and Colitis Foundation using a separate claimsbased dataset [2]. Rapid increases in biologic medication costs have not been limited to inflammatory bowel diseasethis is one the most rapidly expanding current sources of medical expenses across all disease states [3].…”
mentioning
confidence: 75%
“…In this cohort as in most IBD centres worldwide, the majority of patients were of relatively young age and would therefore potentially require biologics, immunomodulators and/or 5‐ASA therapies for decades post‐diagnosis. Drug costs are therefore a huge and growing impost to health payers which cannot be ignored by clinicians and should be mitigated wherever possible . Data assessing clinical outcomes following discontinuation of 5‐ASA therapy with or without concomitant immunomodulating therapy are limited.…”
Section: Discussionmentioning
confidence: 99%